Analisis Judi Online Dalam Perspektif Filsafat Politik Thomas Hobbes - Nuraini, Insania Cahya (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the philosophical practice of online gambling in the view of Thomas Hobbes' philosophy, particularly in his view of human nature. This study uses a qualitative research method based on literature study (research study). The results of this study show that online gamblers reflect the state of nature, which is a natural state where humans act based on their personal interests without effective legal control. Online gambling illustrates the failure of the state as a leviathan to regulate society in the digital realm, thereby weakening the social contract. This is because online gambling addiction can lead to criminality and domestic violence, not to mention mental health issues. In Hobbes's view, humans are rational beings driven by fear, the desire to preserve themselves, and ambition for power. It can be understood that, according to Hobbes, human consciousness is formed from utilitarian consciousness, not moral consciousness, so it is necessary to design measures to instill fear of violations, not just ethical appeals.